Complement C5a‐Induced Changes in Neutrophil Morphology During Inflammation. (September 2017) - Denk, S.; Taylor, R. P.; Wiegner, R.; Cook, E. M.; Lindorfer, M. A.; Pfeiffer, K.; Paschke, S.; Eiseler, T.; Weiss, M.; Barth, E.; Lambris, J. D.; Kalbitz, M.; et al.
Abstract: The complement and neutrophil defence systems, as major components of innate immunity, are activated during inflammation and infection. For neutrophil migration to the inflamed region, we hypothesized that the complement activation product C5a induces significant changes in cellular morphology before chemotaxis. Exposure of human neutrophils to C5a dose‐ and time‐dependently resulted in a rapid C5a receptor‐1 (C5aR1)‐dependent shape change, indicated by enhanced flow cytometric forward‐scatter area values. Similar changes were observed after incubation with zymosan‐activated serum and in blood neutrophils during murine sepsis, but not in mice lacking the C5aR1. In human neutrophils, Amnis high‐resolution digital imaging revealed a C5a‐induced decrease in circularity and increase in the cellular length/width ratio. Biomechanically, microfluidic optical stretching experiments indicated significantly increased neutrophil deformability early after C5a stimulation. The C5a‐induced shape changes were inhibited by pharmacological blockade of either the Cl − / HCO 3 − ‐exchanger or the Cl − ‐channel. Furthermore, actin polymerization assays revealed that C5a exposure resulted in a significant polarization of the neutrophils. The functional polarization process triggered by ATP–P2X/Y‐purinoceptor interaction was also involved in the C5a‐induced shape changes, because pretreatment with suramin blocked not only the shape changes but also the subsequent C5a‐dependent chemotactic activity. In conclusion, the data suggest that the anaphylatoxin C5a regulates basic neutrophil cell processes by increasing the membrane elasticity and cell size as a consequence of actin‐cytoskeleton polymerization and reorganization, transforming the neutrophil into a migratory cell able to invade the inflammatory site and subsequently clear pathogens and molecular debris.